Functional Response of Cycloneda sanguinea (L.) (Coleoptera: Coccinellidae) to the Black Pea Aphid, Aphis craccivora Koch (Hemiptera: Aphididae) - Solano Rojas, Yohan Alexander; Delgado, Nereida; Morales, José; Vásquez, Carlos (ENTOMOTROPICA, 2016)
In this study, we determined feeding response, handling time (Th) and search rate (a) of the ladybeetle Cycloneda sanguinea (L.), with respect to the black pea aphid, Aphis craccivora Koch. The experiments were conducted using larvae and adult males and females reared under laboratory conditions. Various mathematical models were applied to the feeding response data using regression analysis. The Th and a values, were estimated by a nonlinear regression analysis. At the highest density tested, the fourth larval instar (L4) consumed daily an average of 132.2 aphids/cage, compared with the first (L1), second (L2) and the third (L3) larval instars, which consumed 10.6, 35.2 and 72.8 aphids/cage, respectively, while adult females consumed 233.8 aphids/cage and adult males consumed 209 aphids/cage. The functional response curve to L1 adjusted better to the exponential model, while L2, L3, L4, male and female adults adjusted better to linear or type II Holling’s model. The values of Th and a, were higher in L1 and L3, with respect to other larval instars, while in the adult stage, females presented lower Th and greater a, compared with males. We conclude that L4 and adult females are the most voracious stages of C. sanguinea feeding on A. craccivora.